Measurement of the shape of the boson rapidity distribution for pp̄→Z/γ*→e+e-+X events produced at s of 1.96 TeV - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Aguilo, E; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; Alton, A; et al. (2007)
We present a measurement of the shape of the boson rapidity distribution for pp̄→Z/γ*→e+e-+X events at a center-of-mass energy of 1.96 TeV. The measurement is made for events with electron-positron mass 71